Hubungan antara Management Parenting Stress terhadap Tingkat Stres Pengasuhan pada Ibu Muda - Tulhidaya, Azyka; Marhani, Marhani; Bin Anuar, Arman; Kadir, Abdul (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
This study aimed to explore the relationship between parenting stress management and the level of parenting stress among young parents. The research sample consisted of 100 young mothers living in Luwu Regency, aged a maximum of 30 years, having children aged 0–6 years, and currently in a marital relationship. The sampling technique used was purposive sampling. The instrument used to measure parenting stress management was the Coping Orientation to Problem Experienced (COPE). The parenting stress variable was measured using the Parental Stress Scale (PSS). Statistical data analysis employed Pearson’s product–moment correlation analysis. The results showed a negative relationship between the two variables, meaning that the better the parenting stress management of young mothers, the lower the level of parenting stress experienced. Conversely, poorer parenting stress management was associated with higher levels of parenting stress. This finding was supported by a correlation coefficient of (r = −0.625) with a significance value of (sig. = 0.000).